Processing and analysis of chitosan nanocomposites reinforced with chitin whiskers and tannic acid as a crosslinker - Rubentheren, Viyapuri; Ward, Thomas A.; Ching, Yern Chee; Chee, Kuang Tang (Elsevier, 2015)
Chitosan film reinforced with nano-sized chitin whiskers and crosslinked using tannic acid was synthesized by the casting-vaporation method. The mechanical and physicochemical properties of several film samples (consisting of different ratio of chitin and tannic acid) were compared with neat chitosan. Tensile tests show that the addition of chitin improves the nanocomposite films mechanical properties up to 137% compared to neat chitosan, but this is slightly degraded when tannic acid is introduced. However, tannic acid and chitin whisker content greatly reduced moisture content by 294% and water solubility by 13%. Transmission electron microscopy (TEM) and Fourier-transform-infrared spectroscopy (FTIR) were used to investigate the morphology and molecular interaction of film. X-ray diffraction results indicated that the samples with chitin whiskers had a more rigid structure. The addition of tannic acid changed the structure into an anhydrous crystalline conformation when compared to neat chitosan film. (C) 2014 Elsevier Ltd. All rights reserved.